Cholesterol-Ester Transfer Protein Alters M1 and M2 Macrophage Polarization and Worsens Experimental Elastase-Induced Pulmonary Emphysema - Santana, Kelly Gomes; Righetti, Renato Fraga; Breda, Cristiane Naffah de Souza; Domínguez-Amorocho, Omar Alberto; Ramalho, Theresa; Dantas, Francisca Elda B.; Nunes, Valéria Sutti; Tibério, Iolanda de Fátima Lopes Calvo; Soriano, Francisco Garcia; Câmara, Niels O. S.; Quintão, Eder Carlos Rocha; Cazita, Patrícia M. (Frontiers in Immunology, 2021)
Cholesterol-ester transfer protein (CETP) plays a role in atherosclerosis, the inflammatory response to endotoxemia and in experimental and human sepsis. Functional alterations in lipoprotein (LP) metabolism and immune cell populations, including macrophages, occur during sepsis and may be related to comorbidities such as chronic obstructive pulmonary disease (COPD). Macrophages are significantly associated with pulmonary emphysema, and depending on the microenvironment, might exhibit an M1 or M2 phenotype. Macrophages derived from the peritoneum and bone marrow reveal CETP that contributes to its plasma concentration. Here, we evaluated the role of CETP in macrophage polarization and elastase-induced pulmonary emphysema (ELA) in human CETP-expressing transgenic (huCETP) (line 5203, C57BL6/J background) male mice and compared it to their wild type littermates. We showed that bone marrow-derived macrophages from huCETP mice reduce polarization toward the M1 phenotype, but with increased IL-10. Compared to WT, huCETP mice exposed to elastase showed worsened lung function with an increased mean linear intercept (Lm), reflecting airspace enlargement resulting from parenchymal destruction with increased expression of arginase-1 and IL-10, which are M2 markers. The cytokine profile revealed increased IL-6 in plasma and TNF, and IL-10 in broncho-alveolar lavage (BAL), corroborating with the lung immunohistochemistry in the huCETP-ELA group compared to WT-ELA. Elastase treatment in the huCETP group increased VLDL-C and reduced HDL-C. Elastase-induced pulmonary emphysema in huCETP mice promotes lung M2-like phenotype with a deleterious effect in experimental COPD, corroborating the in vitro result in which CETP promoted M2 macrophage polarization. Our results suggest that CETP is associated with inflammatory response and influences the role of macrophages in COPD.